2015
DOI: 10.3389/fmicb.2015.01159
|View full text |Cite
|
Sign up to set email alerts
|

Selective isolation of ammonia-oxidizing bacteria from autotrophic nitrifying granules by applying cell-sorting and sub-culturing of microcolonies

Abstract: Nitrification is a key process in the biogeochemical nitrogen cycle and biological wastewater treatment that consists of two stepwise reactions, ammonia oxidation by ammonia-oxidizing bacteria (AOB) or archaea followed by nitrite oxidation by nitrite-oxidizing bacteria. One of the representatives of the AOB group is Nitrosomonas mobilis species. Although a few pure strains of this species have been isolated so far, approaches to their preservation in pure culture have not been established. Here, we report isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 35 publications
(50 reference statements)
1
28
1
2
Order By: Relevance
“…The cell size and tendency to aggregation vary between species. Although other AOB and NOB isolated from activated sludge by a cell sorting system form single-species microcolonies (32)(33)(34), such microcolonies of Nitrotoga were not found in this study. The enriched Nitrotoga cells were planktonic or aggregated with heterotrophs (Fig.…”
Section: Resultscontrasting
confidence: 69%
“…The cell size and tendency to aggregation vary between species. Although other AOB and NOB isolated from activated sludge by a cell sorting system form single-species microcolonies (32)(33)(34), such microcolonies of Nitrotoga were not found in this study. The enriched Nitrotoga cells were planktonic or aggregated with heterotrophs (Fig.…”
Section: Resultscontrasting
confidence: 69%
“…Out of the AOB genes (Supplementary Figure S1), 61 sequences were collected, and these sequences were clustered into three OTUs. With a 99% similarity for each OTU, as previously predicted [42], Nitrosomonas cluster is usually found in river ecosystems [43]. Our results also confirmed this phenomenon; 99.7% of the total AOB sequences were obtained from S7 and S9 downstream.…”
Section: Discussionsupporting
confidence: 90%
“…The genome included 3075 protein-coding DNA sequences (CDSs), 41 tRNA genes, and a single copy of the 16S-23S-5S rRNA operon. Based on phylogenetic analyses of N. mobilis Ms1 with other AOB (Fujitani et al, 2015), Ms1 showed the greatest similarity to Nitrosomonas sp. strains Nm107 and Nm104 (99.7–100%) at the 16S rRNA and amoA genes levels and 99.6% similarity to Nitrosococcus mobilis Nc2 at the 16S rRNA gene level, therefore Ms1 was attributed to the N. mobilis lineage.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrosomonas mobilis Ms1 isolated from nitrifying granules (Fujitani et al, 2015) was kept in liquid culture of mineral medium containing 30 mg-N L -1 of ammonium substrate (NH 4 Cl) with the following components per liter of distilled water: NaCl (0.116 g), MgSO 4 ⋅7H 2 O (0.4 g), CaCl 2 ⋅2H 2 O (0.073 g), KCl (0.038 g), KH 2 PO 4 (0.034 g), FeCl 2 (0.002 g), EDTA (0.0043 g), MnCl 2 ⋅4H 2 O (0.1 mg), CoCl 2 ⋅6H 2 O (0.024 mg), NiCl 2 ⋅6H 2 O (0.024 mg), CuCl 2 ⋅2H 2 O (0.017 mg), ZnCl 2 (0.068 mg), Na 2 WO 4 ⋅2H 2 O (0.033 mg), Na 2 MoO 4 (0.024 mg), and H 3 BO 3 (0.062 mg). The pH of the culture media was adjusted to 8.0 by NaHCO 3 (0.84 g L -1 ), and phenol red (0.4 w/v %) was used as the pH indicator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation